2018
DOI: 10.1098/rspb.2018.0865
|View full text |Cite|
|
Sign up to set email alerts
|

A trade-off between thickness and length in the zebra finch sperm mid-piece

Abstract: The sperm mid-piece has traditionally been considered to be the engine that powers sperm. Larger mid-pieces have therefore been assumed to provide greater energetic capacity. However, in the zebra finch Taeniopygia guttata, a recent study showed a surprising negative relationship between mid-piece length and sperm energy content. Using a multi-dimensional approach to study mid-piece structure, we tested whether this unexpected relationship can be explained by a trade-off between mid-piece length and mid-piece … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 53 publications
(74 reference statements)
1
31
0
Order By: Relevance
“…Unfortunately, the exact energetic benefits of changes in midpiece morphology under warmer conditions are difficult to ascertain, since past studies have found it to have inconsistent relationships with sperm performance (Bennison, Hemmings, Brookes, Slate, & Birkhead, ) and have mostly focused on internal fertilizers with different reproductive biology to Galeolaria (but see Schlegel, Binet, Havenhand, Doyle, & Williamson, ). Nonetheless, shorter or wider midpieces could potentially reflect beneficial rearrangements in the internal organization of mitochondria (Mendonca et al, ). For instance, denser packing of mitochondrial membranes can allow ATP to be produced more efficiently (Demongeot, Glade, Hansen, & Moreira, ; Mannella, Lederer, & Jafri, ), and larger midpieces can store more energy to enhance sperm swimming performance (Firman & Simmons, ; Lüpold et al, , but see Bennison et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, the exact energetic benefits of changes in midpiece morphology under warmer conditions are difficult to ascertain, since past studies have found it to have inconsistent relationships with sperm performance (Bennison, Hemmings, Brookes, Slate, & Birkhead, ) and have mostly focused on internal fertilizers with different reproductive biology to Galeolaria (but see Schlegel, Binet, Havenhand, Doyle, & Williamson, ). Nonetheless, shorter or wider midpieces could potentially reflect beneficial rearrangements in the internal organization of mitochondria (Mendonca et al, ). For instance, denser packing of mitochondrial membranes can allow ATP to be produced more efficiently (Demongeot, Glade, Hansen, & Moreira, ; Mannella, Lederer, & Jafri, ), and larger midpieces can store more energy to enhance sperm swimming performance (Firman & Simmons, ; Lüpold et al, , but see Bennison et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, shorter or wider midpieces could potentially reflect beneficial rearrangements in the internal organization of mitochondria (Mendonca et al, 2018). For instance, denser packing of mitochondrial membranes can allow ATP to be produced more efficiently (Demongeot, Glade, Hansen, & Moreira, 2007;Mannella, Lederer, & Jafri, 2013), and larger midpieces can store more energy to enhance sperm swimming performance (Firman & Simmons, 2010;Lüpold et al, 2009, but see Bennison et al, 2016).…”
Section: F I G U R Ementioning
confidence: 99%
See 1 more Smart Citation
“…However, even without contractility, the narrow SST orifice (mean diameter of about 315 3 µm), with the added obstruction of microvilli (1-2 µm in length, [52]) could restrict 316 the rate of sperm (mean diameter at mid-piece -~0.6 µm [59]) entering and exiting 317 the SST, thereby providing a mechanism by which sperm storage and release can be 318 regulated. This, combined with the fact that sperm do not appear to actively swim 319 inside or on immediate release from the tubules, supports the idea that avian SSTs 320 play an active and selective role in sperm storage, regulating sperm uptake and 321 release and suppressing motility [33][34][35][36][37][38].…”
Section: Discussion: 308mentioning
confidence: 99%
“…For example, the openSPIM project is highly successful as a tool to train microscopists on how to build and use a light-sheet microscope. However, only a small fraction [16][17][18][19][20][21][22] With the mesoSPIM initiative, we hope to provide a mesoscopic imaging instrument for cleared tissue en par or better than existing options. The setup is thus suitable for research groups or imaging facilities in search of alternatives to the existing palette of commercial instruments.…”
Section: Comparison To Commercial and Open-source Light-sheet Instrummentioning
confidence: 99%